Assessing the Effectiveness of Case-Based Learning on Students' Attitudes Toward Chemistry and Formal Reasoning in Acid-Base Topics - Apriyanti, Adelia; Wiyarsi, Antuni (Jurnal Tadris Kimiya, 2024)
Effective teaching strategies are critical in enhancing students' attitudes toward chemistry and formal reasoning abilities, particularly for complex topics like acids and bases. Case-based learning has emerged as a promising alternative to traditional scientific learning methods. This study aims to compare the differences in attitudes toward chemistry and formal reasoning skills between students exposed to case-based learning and those undergoing scientific learning on acids and bases. A quasi-experimental design with a posttest-only control group was applied to 122 student of 11th grade science students in Yogyakarta, selected using simple random sampling. Data were collected through case-based essay questions and attitude questionnaires. Multivariate analysis (Hotelling Trace) assessed the differences between groups. The analysis revealed a significant difference (p = 0.000 < 0.05) in attitudes and formal reasoning skills between the two groups. Students in the case-based learning group demonstrated significantly better attitudes toward chemistry compared to those in the scientific learning group. These findings highlight the potential of case-based learning to enhance students’ engagement and reasoning skills in chemistry. By integrating case-based approaches into acid-base learning, teachers can adopt alternative methods to improve student outcomes. This study underscores the importance of diversifying teaching strategies to address the challenges of complex scientific topics effectively.